The steam and condensate loop. (Gloucestershire : Spirax Sarco, 2007)
The Steam and Condensate Loop' is an engineer's best practice guide to saving energy and optimising plant performance. This essential book explains the principles of steam engineering and heat transfer, covering all aspects of steam and condensate systems from the boiler house, through the steam distribution system to the point of use, and recovering, and returning condensate back to the boiler. Optimising your plant through best practice energy saving principles can greatly reduce your carbon emissions.With practical application knowledge to deliver energy saving solutions, this indispensable reference guide is a must for all experienced engineers and an invaluable training tool to all those new to steam engineering.
Keywords: Energietechnologie; Stoomtechnieken